Response of cucumber (Cucumis sativus L.) seedlings to exogenous silicon and salicylic acid under osmotic stress - Jafari, Seyyed Reza; Arvin, Seyyed Mohammad Javad; Kalantari, Khosrow Manoochehri (Acta Biologica Szegediensis, 2015)
This study investigates the role of 1.5 mM silicon (Si) and 10 μM salicylic acid (SA) singly or in combination, in inducing cucumber seedlings tolerance to osmotic stress (15% PEG). Osmotic stress reduced shoot fresh and dry mass (SFM, SDM), shoot K+ uptake and leaf area (LA) and increased malondialdehyde (MDA), hydrogen peroxide (H2O2), and ion leakage (IL). Under osmotic stress, Si, SA and Si+SA, increased LA, SFM, SDM, relative water content, total phenolic compounds, anthocyanins, flavonoids, shoot K+ and phenylalanine ammonia lyase (PAL) activity. In all cases the effect of Si+SA was more pronounced. Moreover, Si, SA and Si+SA reduced MDA, H2O2, ion leakage, proline and other aldehydes, under osmotic stress. Meanwhile, under osmotic stress, Si or SA improved seedling performance by enhancing antioxidant enzymes activity, but the better performance of the seedlings under osmotic stress treated with Si+SA was not associated with further enhancement of antioxidant enzymes activity. However, Si+SA treatment significantly increased non-enzymatic antioxidants, total phenolic compounds, anthocyanins, flavonoids, and Si, K+, Ca2+ content in shoot and also PAL activity that might have contributed to higher tolerance of seedling to osmotic stress.